The other frontiers of Arab nationalism: Ibadis, berbers, and the Arabist-Salafi Press in the Interwar period - Ghazal, Amal N. (International Journal of Middle East Studies, 2010)
On Abū Isḥāq Ibr. Iṭfayyish (Cairo), Abū ‘l-Yaqẓān Ibr. (Mīzāb), Hāshil al-Maskarī and his journal al-Falaq in Zanzibar.
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973); Aṭfiyyash, Ibrāhīm b. Muḥammad (1886-1965); Maskarī, Hāshil al-; Réformisme

Khārijism and Ibāḍism: the quest for an integrative approach to Islamic history - Ghazal, Amal N. (Bulletin of the Royal Institute for Inter-Faith Studies, 2005)
Keywords: Kharijisme

Islam and Arabism in Zanzibar: The Omani Elite, the Arab World and the Making of an Identity, 1880s-1930s - Ghazal, Amal N. (University of Alberta, 2005)
Keywords: Zanzibar

The other “Andalus”. The Omani elite in Zanzibar and the making of an identity, 1880s-1930s - Ghazal, Amal N. (MIT Electronical Journal of Middle East Studies, 2005)
Keywords: Zanzibar

Intellectual Traditions, Islamic Reform and Nationalism in the Mzab - Ghazal, Amal N. (THE SOUTHERN SHORES OF THE MEDITERRANEAN AND BEYOND: 1800 - TO PRESENT, 2013)
This paper discusses the role of North African Ibadis, Mzabis in particular, in movements of religious reform and nationalism in the nineteenth and twentieth centuries. It unravels the intellectual networks in which Mzabis had been integrated since the late nineteenth century and that spanned from North Africa to East Africa and Oman. Mzabis’ membership in such networks highlighted the reformist trends within Ibadism that led to a rapprochement with the other sects of Islam. This also consequently facilitated the assimilation of Mzab and of Mzabis into the nationalist movements of Algeria in which Mzabis played a leading and formative role. Sources include manuscripts from the Mzab valley, Mzabi newspapers and French archival material.
Keywords: Réformisme -- Mzab

Islamic reform and Arab nationalism: expanding the crescent from the Mediterranean to the Indian Ocean (1880s-1930s) - Ghazal, Amal N. (Culture and civilization in the Middle East, 2010)
This book examines the relationship between Islam and nationalism and the evolution of identity politics. Bridging African and Arab histories and giving a cross-national and cross-regional analysis of movements of religious reform, nationalism and anti-colonialism, its wide geographical coverage ranges from Zanzibar on the Indian Ocean through to Oman into the Mediterranean
Keywords: Zanzibar

Zanzibar's Liberation between Global 60's and Local politics - Ghazal, Amal N. (MEC Friday Seminars, 2023)
Keywords: Vie politique -- Zanzibar -- 1963-1964

منهجية الشبكة وكتابة التاريخ الحديث، الإبضية مثالا - Ghazal, Amal N. (2018)

Zanzibar: Re-Searching the “Other Andalus” - Ghazal, Amal N. (al-Akhbar, 2013)
Keywords: Zanzibar

Tensions of nationalism: The Mzabi student missions in Tunis and the politics of anticolonialism - Ghazal, Amal N. (International Journal of Middle East Studies, 2015)
Abstract This article examines the significant yet largely overlooked role of the Mzabis, a community from the northern edges of the Algerian desert, in Algerian and Tunisian anticolonialism and nationalism. In so doing, it pursues two aims: first, to shed light on the importance of Tunis to the politicization of the Mzabis in the 1920s and to their induction into local and regional anticolonial and national movements; and second, to highlight the tensions of subsuming regional identities into overarching national identities by focusing on Mzabi political activists’ negotiation of the relationship between the Mzab and Algeria as a national project. The article also explores the spectrum of political possibilities and alternatives envisioned by Mzabis as they participated in religious reform, anticolonial, and nationalist movements. This spectrum, I argue, conveys the fluid relationship between local, national, and regional identities, thus undermining teleological readings of national identity formation.
Keywords: Réformisme -- Mzab

Fatwas, Poetry and Riddles: Ibadis in China in the 17th Century - Ghazal, Amal N. (The 9th Conference on Ibadi Studies: China and the World: Development and Cooperation from the Perspective of the Belt and Road Initiative, 2018)

Oman: Arab historiography and Arab views - Ghazal, Amal N. (The Ibadism of Oman Its Overseas Development and its Perception Overseas, 2011)
Keywords: Récits de voyage -- Oman

Seeking common ground: Salafism and Islamic reform in modern Ibāḍī thought - Ghazal, Amal N. (Bulletin of the Royal Institute for Inter-Faith Studies, 2005)
Keywords: Réformisme

Transcending Area Studies: Piecing Together the Cross-Regional Networks of Ibadi Islam - Ghazal, Amal N. (Comparative Studies of South Asia, Africa and the Middle East, 2014)
The area studies model is an impediment to the historical analysis of linkages and connections not governed by its geographical and conceptual boundaries. Its shortcomings are even more pronounced in the historiography of the modern period, when interactions and exchanges between different communities have changed dramatically, in both scale and scope. In the region loosely defined as the Middle East, the problem is further compounded by the collapse of the Ottoman order and the erection of state borders. The framework of methodological nationalism tied to those borders has been productive of certain kinds of histories and not others. In this intervention, Ghazal takes the case of Ibadis, their geographic distribution, political activism, and patterns of communication, to showcase the shortcomings of area studies as a model of historical analysis. A more viable alternative to spatially bounded analytical frames, Ghazal proposes, is the network.
Keywords: Réformisme

Self-Minoritization: Performing Difference in Colonial Algeria - Ghazal, Amal N. (Comparative Studies of South Asia, Africa and the Middle East, 2021)
This article looks at the process through which the Ibadi Mzabi community in the Algerian desert "minoritized" itself during the colonial period, leading into the 1948 elections to represent the Mzab Valley on the newly created Algerian Assembly. This representation legally and effectively incorporated the Mzab into French Algeria and ended its special status as a French protectorate. Mzabi self-minoritization, Ghazal argues, was a process of performative differentiation based on a sectarian identity. It was initiated by the colonized and negotiated with the colonizer, emerging at the intersection of colonialism and the institutionalization of political representation in colonial Algeria. Ghazal defines this process as self-minoritization to attribute a proactive role for, and more agency to, the colonized in claiming a "minority" identity and negotiating a special status within the colonial order.

Dynamics of Ibadi Reform and the Network as a Methodology - Ghazal, Amal N. (3rd Ibadi Summer School : "Ibadi Islam: A Critical Examination of Sources", 2020)
Keywords: Réformisme

al-Ḥukm al-Būsaʿīdī fī Zinjibār: Naẓra fī Ṣiyāghat Iṭār Jadīd li’l-Fikr al-ʿArabī al-Islāmī - Ghazal, Amal N. (Al-Minhāj, 2011)
Keywords: Zanzibar

Mediating Knowledge: The Circulation of Fatwas between Oman and the Maghreb at the turn of the 20th century - Ghazal, Amal N. (Ibadism and the Study of Islam: A view from the edge, 2019)
Keywords: Réformisme -- Oman

Counter-currents: Mzabi independence, pan-Ottomanism and WWI in the Maghrib - Ghazal, Amal N. (First World War Studies, 2016)

Omani Fatwas and Zanzibari Cosmopolitanism: Modernity and Religious Authority in the Indian Ocean - Ghazal, Amal N. (The Muslim World, 2015)
Keywords: Réformisme -- Zanzibar

al-Nukhba al-ʿUmāniyya fī Zinjibār: Qirā’a fī Maṣādir wa-Uṭur al-Fikr al-Qawmī - Ghazal, Amal N. (al-Mu’tamar al-Duwalī : al-Dawr al-ʿUmānī fī ‘l-Sharq al-Ifrīqī, 11-13 Dec. 2012. Buḥūth al-Mu’tamar, 2014)

Lamkī, Aḥmad al- - Ghazal, Amal N. (Encyclopaedia of Islam, 2015)
Keywords: Biographies -- Oman

L'Aventure Ibadite dans le Sud Tunisien: Effervescence d'une région méconnue (VIIIe-XIIIe siècle) - Ghazal, Amal N. (Der Islam, 2013)
Keywords: Nukkarisme; Recension

Omani fatwas and Zanzibari cosmopolitanism: modernity and religious authority in the Indian Ocean - Ghazal, Amal N. (The Fatwa As an Islamic Legal Instrument: Concept, Historical Role, Contemporary Relevance, 2018)

Politics and Polemics. Ibāḍī Theology in North Africa in the Modern Period - Ghazal, Amal N. (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Réformisme

Zanzibar and East Africa Through Local Eyes: al-Mughayrī’s Juhaynat al-Akhbār - Ghazal, Amal N. (Today's perspectives on Ibadi history, 2017)
Keywords: Zanzibar

Islamic Reform and Arab Nationalism. Expanding the Crescent from the Mediterranean to the Indian Ocean (1880s-1930s) - Bang, Anne K. (Journal of Islamic Studies, 2013)
Keywords: Recension

تعليق وإحاطة سياقية على هامش محاضرة د. أمل غزال حول بعض مضامين محاضرتها بعنوان: التكوين الذاتي للأقلية: المزابيون وأداء الاختلاف في المستعمر الفرنسية" - حجاج, قاسم بن حمو (2022)
تعتبر الدراسات المتعلقة بتاريخ الأفكار والأيديولوجيات مجال خصب تحليل الأوضاع والتوجهات الماضية والحاضرة والمستقبلية للمجتمعات، وبالاستناد إلى تدريسي الطويل لمادة الفكر السياسي الحديث والمعاصر ولمادة الأقليات والأمن الدولي. ولما كانت الباحثة قد اشتغلت في مراكز أبحاث أمريكية على الأقليات وخاصة الجماعة المزابية في شمال إفريقيا فإنه لا يمكن استبعاد الدور التمهيدي لمثل هذه لمشاريع البحثية على سياسات القوى الكبرى وحتى الإقليمية كقطر وإسرائيل والإمارات في صنع الأقليات والتلاعب بالتركيبات المجتمعية، علما أن للباحثة أعمال علمية سابقة منشورة عن المزابيين منها دورهم في شمال إفريقيا إبان الحرب العالمية الثانية وعلاقاتهم الخارجية بدويلة طرابلس وبتونس...

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition By Paul M. Love Jr - Ghazal, Amal N. (Journal of Islamic Studies, 2021)
Typically, siyar in the Islamic tradition are biographical texts outlining the life and times of individuals, whether scholars or otherwise. Siyar are not known to offer coherent historical narratives, nor are they complete historical chronicles. They are usually compiled in an incremental manner, passing from one generation to another, creating a chain of individuals and/or communities across time and space. Despite their prominence, they have mostly served the historical profession, more or less, as biographical dictionaries. Ibadi siyar in North Africa belong to this same genre and have served a similar purpose. Paul Love’s book uses an innovative methodology in his analysis of siyar that changes the way historians can use and read these texts.
Keywords: Recension

Science and Education: An Ibāḍī Project of Reform - Ghazal, Amal N. (Local and global Ibadi identities, 2019)
Keywords: Réformisme

Transmission of Ibāḍī Knowledge: Between China and Oman - Ghazal, Amal N. (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

الاقلية الذاتية للمنزابيين في الفترة الاستعنارية عزض ومناقشة: الجزء الأول - خواجة, عبد العزيز بن محمد (2022)
Keywords: Recension

The Individual Reaction to Western Modernization - Ghazal, Amal N. (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

An Ottoman Pasha and the End of Empire: Sulayman al-Baruni and the Networks of Islamic Reform - Ghazal, Amal N. (Global Muslims in the Age of Steam and Print, 2014)
Keywords: Bārūnī, Sulaymān al- (1870-1940); Réformisme

Ibadi Jurisprudence: Responses to Modernity - Ghazal, Amal N. (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh

Oman: The Arab Views - Ghazal, Amal N. (Oman and overseas, 2013)

Debating Slavery and Abolition in the Arab Middle East - Ghazal, Amal N. (Slavery, Islam and diaspora, 2009)
Keywords: Esclavage -- Zanzibar